Change of prognosis of patients with myelodysplastic syndromes during the last 30 years. Issue 7 (July 2015) - Neukirchen, Judith; Nachtkamp, Kathrin; Schemenau, Jennifer; Aul, Carlo; Giagounidis, Aristoteles; Strupp, Corinna; Kuendgen, Andrea; Kobbe, Guido; Haas, Rainer; Germing, Ulrich
Highlights We analyzed the survival of MDS patients diagnosed since 1982. We found a significant longer survival in those patients diagnosed since 2002. The survival benefit was seen especially in high-risk patients. It was also evident in patients receiving best supportive care. We assume a multifactorial cause, especially an improvement of BSC.